Aktualisasi Kaidah I’tibar al-Masalih dalam Pemikiran Izz al-Din Ibn Abd al-Salam - Huzaimah Al-Anshori. (MAHAKIM Journal of Islamic Family Law, 2018)
Goodness actualization in the thought of imam Izz al-Din in triggering the law is not separated fromattracting good and avoiding destruction, a concept that indicates the benefit of mankind. This if weactualize it in the comunity, it will appear that goodness is a priority in assisting a law that will betriggered, provided that it does not conflict with the qur’an agreement, analogy, and istidian of the mu’tabar. maslahah (goodness) in a marriage registration, it has been mentioned in the books of fiqh. Theregulation of it is an anticipatory step from the state (goverment) to anticipate the actions that harm inone side, especially women. This is accordance with the rules. Meaning: the actions of leader/govermentfor the society are to realize the goodness. Imam izz al-Din makes the Holy Qur’an and the hadith as ajuridical basis in establishing a law. Besides that, Izz al-Din in responding to mas}lah}ah as a reference inlaw istinbat he rests on istidlal al-sahih or with the term istidlal bi al-masalih.